The role of Prince Khaled and the Algerian immigrants in the emergence of the revolutionary independence movement in Algeria 1924 – 1926 - hamdi, amar; sarri, Ahmed (The Algerian Historical Journal, 2026)
During the post-World War I period, the Algerian Muslim elites aspired to engage in political action, under the banner of a national party made up of the Islamic element. The post-World War I reforms and conditions also contributed to improving the political situation in Algeria, but the colonial administration stopped this when Prince Khaled was exiled from Algeria. With the echo of Prince Khaled’s activity in France, and the heavy presence of Algerian immigrants in France, who benefited from the margin of freedom in France, the national cause found an outlet for it, and the immigrants were able to establish the North African Star, which was considered the first Algerian national revolutionary party, and historians differ in opinions about who is credited with Introducing the idea and establishing the party. In this research paper, we try to study the issue.